Are Temperate Alpine Plants With Distinct Phenology More Vulnerable to Extraordinary Climate Events Than Their Continuously Flowering Relatives in Tropical Mountains? - Křenová, Zdenka; Kindlmann, Pavel; Shelly, J. Stephen; Sklenář, Petr; Sivila, Susanne; Bílá, Karolína; Jaramillo, Ricardo (Frontiers in Ecology and Evolution, 2022)
Alpine plants are perceived as some of the most vulnerable to extinction due to the global climate change. We expected that their life history strategies depend, among others, on the latitude they live in: those growing in temperate regions are likely to have a distinct phenology with short seasonal peaks, while tropical alpine plants can potentially exploit favorable year-round growing conditions and different individuals within a population may flower at different times of the year. In species, whose flowering is synchronized into short seasonal peaks, extraordinary climate events, which may become stronger and more frequent with climate change, can potentially destroy reproductive organs of all synchronized individuals. This may result in reducing fitness or even extinction of such species. We studied field populations of five groups of closely related Andean alpine plant species to test our expectations on their latitude-dependent synchronization of flowering. Our results confirmed these expectations: (i) Tropical alpine species were least synchronized and flowering peaks of different individuals in their populations were distributed across many months. Thus, in tropical alpine species, if an extraordinary event happens, only some individuals are affected and other members of the population successfully reproduce in other parts of the long season. (ii) Higher synchronicity in flowering of temperate and subtropical alpine plants resulted even in some of these species using only a part of the short growing season to reproduce, which increases their vulnerability to extraordinary climatic events. However, we did not find any unique pattern valid for all species, groups and regions. The diversity in flowering phenology (i.e. different levels of seasonality and synchronicity) that we found increases the likelihood of plants successfully coping with climate change.